Advances in Communication, Devices and Networking Proceedings of ICCDN 2018 - Bera, Rabindranath; Sarkar, Subir Kumar; Singh, Om Prakash; Saikia, Hemanta (Lecture Notes in Electrical Engineering, 2019)
The book covers recent trends in the field of devices, wireless communication and networking. It presents the outcomes of the International Conference in Communication, Devices and Networking (ICCDN 2018), which was organized by the Department of Electronics and Communication Engineering, Sikkim Manipal Institute of Technology, Sikkim, India on 2-3 June, 2018. Gathering cutting-edge research papers prepared by researchers, engineers and industry professionals, it will help young and experienced scientists and developers alike to explore new perspectives, and offer them inspirations on addressing real-world problems in the field of electronics, communication, devices and networking.